Multilevel design optimisation of a vehicle-dummy model under crash, vibration and injury criteria. (2016) - Gandikota, Imtiaz; Rais-Rohani, Masoud; Kiani, Morteza; DorMohammadi, Saber
A decomposed formulation and solution approach is presented for multidisciplinary vehicle design optimisation under crashworthiness, occupant safety, mass, and vibration design criteria. The vehicle model, equipped with a dummy and occupant restraint system, is used in nonlinear transient dynamic finite element simulations of both full frontal impact (FFI) and side impact (SI) for calculation of multiple injury criteria. A body-in-white vehicle model based on the corresponding crash finite element model is used for vibration analysis. The hierarchically decomposed multilevel optimisation problem consists of an injury criteria minimisation problem at the system level and separate mass minimisation problems subject to FFI and SI criteria at the subsystem level. Key aspects of the multilevel optimisation methodology are presented with the results showing a mass reduction of 8.7 kg in the vehicle model along an 8% improvement in the injury index with no loss of vehicle rigidity relative to the baseline model.